Cottonseed Meal as Substitute for Soyabean Meal in Broiler Ration - Ojewola, G.S.; Ukachukwu, S.N.; Okulonye, E.I. (International Journal of Poultry Science, 2006)
In a 6 week feeding trial, cottonseed meal was substituted for soyabean meal at 0,25, 50, 75 and 100% and the diets were respectively designated as diets 1, 2, 3, 4 and 5 in a completely randomized design. Biologic and economic performance were investigated. Birds were fed and watered ad-libitum. The results showed that there were no significant differences (P>0.05) in the bird`s mean daily weight gain and feed-to-gain ratio while the mean daily feed intake was significantly (P< 0.05) influenced. Birds fed diets 3 and 4 respectively consumed 150.93g and 153.68g. This was closely followed by diets 5 and 2. Numerically, birds fed diet 3 gave the highest weight gain (2666.6g) while diet 1 was the least (2443.27g). The nutrient utilization analysis showed significant differences (P< 0.05). Diet 5 had the highest percent mean values for nitrogen (81.45), crude fibre (60.81), ether extract (95.57), ash (66.79) and dry matter (85.72) retentions while birds fed diet 1 was least for same parameters. Mineral utilization followed the same trend; diet 5 was the highest (69.08), (84.72), (71.91), (79.39) for phosphorous, potassium, calcium and magnesium respectively while diet 1 gave least values for same parameters. Diet 5 was found to be the cheapest (N290.01) and savings were significantly (P< 0.05) improved with the use of this diet while diets 1 and 3 had the least values of N285.94 and N302.67 respectively for marginal revenue. Though, the diets were comparable, diet 5 showed superior indices for nutrient utilization and economics of production. In conclusion, there is an indication that iron treated cotton seed meal can serve as a substitute for soyabean meal in broiler diet.